Kemampuan TPACK Mahasiswa PPL Program Studi PPG Pendidikan Matematika Universitas Negeri Makassar - Arwadi, Fajar; Haris, Hasnawi; Fudhail, Ahmad; Afriansyah, Ekasatya Aldila; Zaki, Ahmad (Issues in Mathematics Education (IMED), 2024)
This study aims to analyze the TPACK (Technological Pedagogical Content Knowledge) abilities of students in the Teaching Practice Program (PPL) of the Mathematics Education Study Program at the State University of Makassar, specifically in integrating content knowledge, pedagogy, and technology in teaching practices. The study uses a quantitative approach with a descriptive design to describe the level of TPACK mastery among the students. Data were collected from 30 students through a questionnaire designed to measure the three main aspects of TPACK: content knowledge (CK), pedagogical knowledge (PK), and technological knowledge (TK), as well as the students' ability to combine these three aspects in planning and implementing mathematics teaching. The results show that the students in the PPL Program of the PPG Study Program demonstrated good TPACK knowledge, as indicated by scores where 53% of students were in the high category and 47% in the medium category.